2015
DOI: 10.3233/thc-150953
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting success of an integrated community-based telehealth system

Abstract: Abstract. BACKGROUND:The rise of chronic and degenerative diseases in developed countries has become one critical epidemiologic issue. Telehealth can provide one viable way to enhance health care, public health, and health education delivery and support. OBJECTIVE: The study aims to empirically examine and evaluate the success factors of community-based telehealth system adoption. METHODS: The valid 336 respondents are the residents of a rural community in Taiwan. The structural equation modeling (SEM) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Only one study, involving 336 participants in a rural community in Taiwan, found that among three intrinsic qualities considered (i.e. system, information and service quality), system quality had the strongest overall positive effect on the intention to use telehealth (Hsieh et al., 2015). Zhou et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study, involving 336 participants in a rural community in Taiwan, found that among three intrinsic qualities considered (i.e. system, information and service quality), system quality had the strongest overall positive effect on the intention to use telehealth (Hsieh et al., 2015). Zhou et al.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic quality of the technology was investigated in relation to system quality, information quality and service quality (e.g. Hsieh, Tsai, Chih, & Lin, 2015), as well as the quality of healthcare (e.g. Peeters, de Veer, van der Hoek, & Francke, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…As means of interpretation of findings and implications for clinical practice, various dimensions of satisfaction were generated: system experience, information sharing, consumer focus and overall satisfaction. These dimensions were adapted from a research model shown to influence users’ satisfaction in a community-based telehealth program [27]. The model proposed by Hsieh et al .…”
Section: Methodsmentioning
confidence: 99%
“…The model proposed by Hsieh et al . [27] provided a framework to synthesise the data for this systematic review given the paucity of literature that defines the construct of satisfaction with telehealth.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire ( Fig. 1) assessing different dimensions of satisfaction 5,[7][8][9][10] was created, which included demographic and neurology follow-up details, expenses incurred for in-person visit for transportation and lodging (cost savings with tele-consult), 9 dichotomous scale items to assess satisfaction, and a 5-point Likert scale item for overall satisfaction. Furthermore, to compare tele-consult experience with in-person experience, we also asked for the patients' future preference toward telemedicine or in-person consultations, along with subjective reasons for their choice.…”
Section: Methodsmentioning
confidence: 99%